Chronic sleep reduction in adolescents—clinical cut‐off scores for the Chronic Sleep Reduction Questionnaire (CSRQ). (17th January 2018) - Dewald‐Kaufmann, Julia F.; Bruin, Eduard J.; Smits, Marcel; Zijlstra, Bonne J.H.; Oort, Frans J.; Meijer, Anne Marie
Summary: The Chronic Sleep Reduction Questionnaire is a validated questionnaire that measures symptoms of prolonged insufficient and/or poor sleep and therefore accounts for individuals' sleep need and sleep debt. This study extends its psychometric properties by providing cut‐off scores, using a matched sample of 298 healthy adolescents (15.38 ± 1.63 years, 37.9% male, mean Chronic Sleep Reduction Questionnaire score: 32.98 ± 6.51) and 298 adolescents with insomnia/delayed sleep–wake phase disorder (15.48 ± 1.62 years; 37.9% male, mean Chronic Sleep Reduction Questionnaire score: 42.59 ± 7.06). We found an area under the curve of 0.84 (95% confidence interval: 0.81–0.87). Cut‐off scores for optimal sensitivity, optimal specificity and based on Youden's criterion are provided. These cut‐off scores are highly relevant for use of the Chronic Sleep Reduction Questionnaire in future studies and clinical practice.